Sustainability and the civil commons : rural communities in the age of globalization - Sumner, Jennifer, 1949- (University of Toronto Press, 2005)
"Sustainability and the Civil Commons" moves beyond rural roots to build a comprehensive understanding of sustainability that combines global reach with local focus.